Minat Baca Siswa Ditinjau Dari Persepsi Keterlibatan Orangtua Dalam Pendidikan - Roy Gustaf Tupen Ama (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
Abstract: Reading interest is very important to grow from an early age in elementary school because with reading interest students will get a lot of knowledge from reading. This study aimed  to determine the correlations between between perceptions of parental involvement in education and students' reading interest. The research method used is a quantitative correlation approach. In this study, the researcher used some scales, namely scale of perceptions of parental involvement in education, and scale of students' interest in reading. The population of this study was all third, fourth, and fifth grade students of Triharjo State Elementary School in Sleman, with a total sample of 124 students. The sampling technique used was purposive sampling with a sample size of 124 students with the sample criteria, namely students in grade 3,4 and 5, male and female and live with their parents. To analyze the  hypothesis the Product Moment correlation technique was used. The results of the analysis show that there is a correlation between perceptions of parents' involvement and students' reading interest with an r value of 0.697.  The results of this study indicate that students' reading interest is in the medium category, it is obtained from the classification results for the medium category as much as 80.6%, and students have a high perception of parental involvement in education as much as 51.6%. Abstrak: Minat baca merupakan hal penting penting untuk di tumbuhkan sejak dini khususnya pada siswa sekolah dasar, karena dengan adanya minat baca siswa-siswi akan mendapat banyak pengetahuan dari membaca. Penelitian ini bertujuan untuk mengetahui hubungan antara persepsi keterlibatan orangtua dalam pendidikan dengan minat baca siswa. Metode penelitian yang digunakan yaitu  pendekatan kuantitatif korelasional. Dalam penelitian ini, peneliti menggunakan skala yaitu skala minat baca dan skala persepsi keterlibatan orangtua dalam pendidikan. Populasi dalam penelitian ini  adalah seluruh siswa kelas 3,4, dan 5 di SDN Triharjo Sleman. Teknik pengambilan sampel yang digunakan adalah purposive sampling dengan jumlah sampel adalah 124 siswa dengan kriteria sampel yaitu siswa kelas 3, 4 dan 5, laki-laki dan peremuan serta tinggal bersama orangtua. Teknik analisis dalam penelitian ini menggunakan teknik korelasi product moment. Hasil analisis menunjukkan bahwa  ada hubungan antara persepsi keterlibatan orangtua dalam pendidikan dengan minat baca siswa, nilai r = 0,697. Hasil penelitian ini menunjukkan  bawa minat baca siswa berada pada  kategori sedang sebanyak  80,6%, dan siswa memiliki persepsi keterlibatan orangtua dalam pendidikan yang tinggi sebanyak 51,6%.